Hinting a dark matter nature of Sgr A* via the S-stars. Issue 1 (20th May 2021) - Becerra-Vergara, E A; Argüelles, C R; Krut, A; Rueda, J A; Ruffini, R
ABSTRACT: The motion data of the S-stars around the Galactic Centre gathered in the last 28 yr imply that Sgr A* hosts a supermassive compact object of about 4 × 10^6 M_, a result awarded with the Nobel Prize in Physics 2020. A non-rotating black hole (BH) nature of Sgr A* has been uncritically adopted since the S-star orbits agree with Schwarzschild geometry geodesics. The orbit of S2 has served as a test of general relativity predictions such as the gravitational redshift and the relativistic precession. The central BH model is, however, challenged by the G2 post-peripassage motion and by the lack of observations on event-horizon-scale distances robustly pointing to its univocal presence. We have recently shown that the S2 and G2 astrometry data are better fitted by geodesics in the spacetime of a self-gravitating dark matter core–halo distribution of 56 keV-fermions, ' darkinos ', which also explains the outer halo Galactic rotation curves. This letter confirms and extends this conclusion using the astrometry data of the 17 best-resolved S-stars, thereby strengthening the alternative nature of Sgr A* as a dense core of darkinos.